Noninvasive Deep Brain Stimulation via Temporally Interfering Electric Fields - Grossman,N; Bono,D; Dedic,N; Kodandaramaiah,SB; Rudenko,A; Suk,H-J; Cassara,AM; Neufeld,E; Kuster,N; Tsai,L-H; Pascual-Leone,A; Boyden,ES (CELL, 2017)
We report a noninvasive strategy for electrically stimulating neurons at depth. By delivering to the brain multiple electric fields at frequencies too high to recruit neural firing, but which differ by a frequency within the dynamic range of neural firing, we can electrically stimulate neurons throughout a region where interference between the multiple fields results in a prominent electric field envelope modulated at the difference frequency. We validated this temporal interference (TI) concept via modeling and physics experiments, and verified that neurons in the living mouse brain could follow the electric field envelope. We demonstrate the utility of TI stimulation by stimulating neurons in the hippocampus of living mice without recruiting neurons of the overlying cortex. Finally, we show that by altering the currents delivered to a set of immobile electrodes, we can steerably evoke different motor patterns in living mice.